Improvement of perennial plants root-zone physical environment caused by soil class-specific deep tillage methods - Azevedo, Raphael Passaglia (2022)
Soil preparation promotes structural changes that creates a favorable environment for the development of cultivated plants. Changes in soil physical properties due to tillage are widely reported in the literature, but information on deep tillage methods, especially in tropical soils, is scarcely reported. Furthermore, the different morphogenetic structures arising from different soil classes provide different physical environments. In this context, the main question that guided this study was: will soils whose structures are morphogenetically different, when under the same tillage, present a similar physical environment? Thus, the hypothesis of this study is that the effect of tillage on the physical environment of the soil is subject to the influence of the intrinsic attributes of the soil class. The objective was to evaluate the effect of tillage practices, considering deep tillage strategies, on the physical quality of the soil and how these effects differ in the three classes of soils with morphogenetically contrasting structures. The experimental area is located in the state of Minas Gerais, Brazil. The evaluated soils were Cambissolo/Typic Dystrustept, Argissolo/Rhodic Hapludult and Latossolo/Rhodic Hapludult. Soil preparations were: MT: surface furrowing (0.1 m) + plant hole (0.4 x 0.7 m); CT: plowing followed by two diskings (0.25 m) + furrowing (0.25 m); SB: plowing followed by two diskings + subsoiling (0.45 m); DM: plowing followed by two diskings + rotary hoe (0.6 m); and DM+Ca: plowing followed by two diskings + rotary hoe (0.6 m) + additional limestone. Soil bulk density, soil resistance to penetration, soil electrical resistivity, visual assessment of soil structure, physical indicators derived from pore size distribution and least limiting water range were evaluated. Resistivity was positively correlated with soil density across the entire dataset, across all soil classes, and individually in Typic Dystrustept with penetration resistance. This confirms the potential for identifying structural changes caused by deep tillage in tropical soils. The indicators that best separated the treatments were aeration capacity, relative field capacity, macroporosity, soil density and S index. The inclusion of critical soil moisture to determine the critical optimal water range allowed greater accuracy in defining the range of water content in the soil without limitations to plants. The soil classes responded differently to the tillage applied, confirming the tested hypothesis. The results made it possible to suggest a specific preparation for each soil class, thus: Deep Mixing till (DM) for the Typic Dystrustept (CX), Subsoiling (SB) ou Deep Mixing till (DM) for the Rhodic Hapludult (PV) e Conventional till (CT) for the Rhodic Hapludult (LV).